News framing of e-cigarettes: A cross-national study of the US, UK, and Korea. Issue 5 (3rd September 2021) - Kang, Jin-Ae; Schulz, Peter; Hubbard, Glenn T.; Hwang, Jooyun; Muldrow, Adrienne; Barber, Brenna; Lochner, Catherine
ABSTRACT: This study explores the growing news coverage of e-cigarettes regarding, (a) how the arguments regarding e-cigarettes are presented in the print news media in the United States (US), United Kingdom (UK), and Korea; (b) which arguments were under-represented; and (c) to what extent scientific research shapes the arguments. Results suggest that the most salient argument in the US and UK was that e-cigarettes are less harmful (or "safer") than regular cigarettes. Although both US and UK news recognized e-cigarettes as a smoking cessation tool, US news framed e-cigarettes from a negative viewpoint. In Korean news, the dominant argument concerned e-cigarette ingredients. The public health frame competed against economic frames in Korean media coverage. With the exception of epidemiological data, scientific studies received very little media coverage in all three countries. Reports of scientific uncertainty were correlated with the level of controversy on e-cigarette issues, and limitations of scientific studies were described to highlight such controversy. Lastly, we discussed issues that were neglected in the news regarding e-cigarettes in all three countries.